Hybrid graphene aerogel intermedium for bendable supercapacitor electrode. (1st October 2018) - Mi, Jinbo; Wang, Yongliang; Han, Zhidong
Abstract : Porous structure materials indicate brilliant distribution and great absorption ability, that suggesting the potential application of aerogel state graphene based materials. Aerogel intermedium assisted method was developed and optimised to prepare bendable electrode. Hydrothermal schedule was utilised suggesting potential application at low cost and large‐scale factory print issues, rather than consuming high money cost and long labour time. Nickel sulphide has been anchored onto the graphene aerogels via one‐pot hydrothermal method. The membrane electrode was made with the carbon ink and aerogel intermedium on the Poly(ethylene terephthalate) (PET) plate. The bendable electrode was fabricated with intermedium and commercial carbon ink, and indicates good performance and economic consumption. The complex membrane capacitor shows the much more brilliant performance than the pure carbon membrane capacitor, with specific capacitance (31.40 mF/cm 2 at 4 mV/s and 17.74 mF/cm 2 at 2 mA/cm 2 ).